From Drafting to Publication: A Systematic Review on Genre-Based Pedagogy in EFL Academic Writing Instruction - Impiani Zagoto; Suhono Suhono; Lies Dian Marsa Ndraha (CV. Creative Tugu Pena, 2025)
This systematic review examines the application of genre-based pedagogy in English as a foreign language (EFL) academic writing instruction between 2015 and 2025. It addresses persistent challenges faced by learners, particularly their limited familiarity with academic genres and difficulties in managing disciplinary writing conventions. Genre-based pedagogy, which foregrounds explicit instruction in genre structures and communicative purposes, has gained recognition as an effective framework for enhancing learners’ academic writing competence. Through a systematic search of peer-reviewed studies indexed in Scopus, this review synthesizes evidence on instructional approaches, learning outcomes, and teaching contexts. Findings reveal that genre-based instruction has been widely implemented in secondary and tertiary education, consistently leading to improved writing performance. Gains are especially evident in organization, cohesion, and genre awareness, alongside increased learner motivation, engagement, and confidence. The reviewed studies employed diverse models, ranging from traditional genre cycles and process-oriented strategies to technology-supported approaches using digital platforms. This diversity highlights the adaptability of genre-based pedagogy and its compatibility with learner-centered instruction. Nonetheless, significant gaps remain: most studies are short-term, emphasize conventional essay genres, and give limited attention to multimodal or interdisciplinary writing. Moreover, inadequate teacher preparation, particularly among preservice educators, continues to hinder effective implementation. To strengthen future research and practice, the review recommends longitudinal studies, broader genre coverage, and systematic teacher training. Overall, the synthesis affirms genre-based pedagogy as a flexible and dynamic approach that fosters both cognitive development and affective engagement in EFL academic writing.